A novel Pickering emulsion stabilized solely by hydrophobic agar microgels. (1st December 2022) - Xiao, Qiong; Chen, Zizhou; Xie, Xiangji; Zhang, Yonghui; Chen, Jun; Weng, Huifen; Chen, Fuquan; Xiao, Anfeng
Abstract: A novel agar-based Pickering emulsion stabilizer was developed through the hydrophobic modification and microgelation of agar. After hexanoylation, the three-phase contact angle of hexanoylated agar (HAG) particles was adjusted from approximately 60° to 96° closing to neutral wettability. After microgelation, the particle size of the modified agar microgel was approximately 2 μm and Zeta potential reached −23.63 mV. Confocal laser microscopy and cryogenic scanning electron microscopy showed that HAG microgels formed a gel network or embedded on the surface of oil droplets, thus providing a dense barrier for oil droplets to coalesce and Ostwald ripening. The oil volume fraction and particle concentration had a significant effect on the droplet size and rheological properties of the Pickering emulsion. Pickering emulsion gels with long-term storage stability was prepared at low particle concentrations (0.7 wt%) and lower oil fractions (φ = 0.3– 0.5), which might become a new effective delivery system for bioactive substances. Graphical abstract: Unlabelled Image Highlights: Agar was designed as a new Pickering emulsifier by hexanoylation and microgelation. Pickering emulsion structure was adjusted by oil fraction and microgel concentration. Pickering emulsion can be stabilized by self-assembly gel networks via agar microgels. Emulsion gels can be formed at low concentration microgels and low oil phase.